Pengembangan Sistem Evaluasi OSCE Berbasis Aplikasi Ponsel untuk Mahasiswa Kedokteran di Indonesia - Rafiq, Azhar; Dirja, Bayu Tirta; Kadriyan, Hamsu; Rohadi, Rohadi (Universitas Mataram, 2024)
Evaluation of Objective Structured Clinical Examination (OSCE) is required to assess medical students’ skills in order to meet the Indonesian medical doctor competency standards. This study presents an innovative method for developing a mobile app-based OSCE evaluation system in Med Stud Games (MSG) and explores its condition. To evaluate MSG, we use the focus group discussion (FGD) method. We use a purposeful sampling approach, consisting of a content expert, medical education expert and medical students. The result of an experience in using MSG for two OSCE training was discussed in FGD. Data was analyzed using in vivo coding and divided into categories to advantages, problems, content, interface, and future improvements. The FGD results in 19 codes. Advantages are categorized as easy to use, fast, practical, and automation timer and scoring. Problems categorized in distraction potential of incoming calls and notifications and online only. Content results in the validity of score and checklist quality. Interface results in font size and layout. Future improvement results in saving and sharing data, open feedback and text, and user-generated content. MSG improve assessment and feedback qualities for medical students. Further observational studies are needed to assess OSCE validation to be used in exam settings